Design and synthesis of environmentally sensitive fluorescent 2-naphthylethynylated 2′-deoxyadenosines: Detection of target DNA via changes in fluorescence intensity and wavelength. Issue 2 (15th January 2016) - Suzuki, Azusa; Kozakai, Ryota; Aso, Tatsuya; Saito, Isao; Takeda, Takuya; Saito, Yoshio
Graphical abstract: Abstract: Various C2-naphthylethynylated 2′-deoxyadenosines were synthesized as environmentally sensitive fluorescent (ESF) nucleosides and their photophysical properties were examined. Among the ESF nucleosides synthesized, four exhibited strong solvatochromicity, two of which were incorporated into oligodeoxynucleotides (ODNs). These ODN probes were able to detect target DNA through distinct changes in fluorescence intensity and wavelength and acted as effective reporter probes.